(untitled) (Scientific journal of the Fergana State University, 2023)
The article is devoted to the culture of Kangyuy on the basis of historical data from Chinese written sources and archaeological excavations in Central Asia, the location of the Kangyuy culture, their names in Chinese sources, comparisons of findings of various cultures and their influences are revealed